Synergetic mechanism and enantioseparation of aromatic β‐amino acids by biphasic chiral high‐speed counter‐current chromatography. Issue 12 (25th May 2016) - Han, Chao; Luo, Jianguang; Li, Zhongrui; Zhang, Yingqi; Zhao, Huijun; Kong, Lingyi
Abstract : A biphasic chiral recognition system based on chiral ligand exchange with Cu(II)‐ N ‐ n ‐dodecyl‐L‐proline and hydroxypropyl‐β‐cyclodextrin as an additive was developed to enantioseparate aromatic β‐amino acids by high‐speed counter‐current chromatography. The biphasic chiral recognition system was established with an n ‐butanol/water (1:1, v/v) solvent system by adding N ‐ n ‐dodecyl‐L‐proline and Cu(II) ions to the organic phase and hydroxypropyl‐β‐cyclodextrin to the aqueous phase. Several separation parameters, such as temperature, pH value, and chiral selector concentration, were systematically investigated by enantioselective liquid–liquid extraction. Under the optimal separation conditions, 54.5 mg of ( R, S )‐β‐phenylalanine and 74.3 mg of ( R, S )‐β‐3, 4‐dimethoxyphenylalanine were baseline enantioseparated. More importantly, the synergistic enantiorecognition mechanism, based on the Cu(II)‐ N ‐ n ‐dodecyl‐L‐proline and hydroxypropyl‐β‐cyclodextrin, was discussed for the first time.